VMP1 Establishes ER-Microdomains that Regulate Membrane Contact Sites and Autophagy. - Luis-Carlos Tábara; Ricardo Escalante (PLoS ONE, 2016)
The endoplasmic reticulum (ER) regulates organelle dynamics through the formation of membrane contact sites (MCS). Here we describe that VMP1, a multispanning ER-resident protein involved in autophagy, is enriched in ER micro-domains that are in close proximity to diverse organelles in HeLa and Cos-7 cells. These VMP1 puncta are highly dynamic, moving in concert with lipid droplets, mitochondria and endosomes. Some of these micro-domains are associated with ER sliding events and also with fission events of mitochondria and endosomes. VMP1-depleted cells display increased ER-mitochondria MCS and altered mitochondria morphology demonstrating a role in the regulation of MCS. Additional defects in ER structure and lipid droplets size and distribution are consistent with a more general function of VMP1 in membrane remodeling and organelle function. We hypothesize that in autophagy VMP1 is required for the correct morphogenesis of the omegasome by regulating MCS at the site of autophagosome formation.